2020
DOI: 10.1155/2020/2868373
|View full text |Cite
|
Sign up to set email alerts
|

S100A12 in Digestive Diseases and Health: A Scoping Review

Abstract: Calgranulin proteins are an important class of molecules involved in innate immunity. These members of the S100 class of the EF-hand family of calcium-binding proteins have numerous cellular and antimicrobial functions. One protein in particular, S100A12 (also called EN-RAGE or calgranulin C), is highly abundant in neutrophils during acute inflammation and has been implicated in immune regulation. Structure-function analyses reveal that S100A12 has the capacity to bind calcium, zinc, and copper, processes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 85 publications
0
34
0
Order By: Relevance
“…The majority of extracellular S100 proteins interact with the receptor for advanced glycation end products (RAGE) and Toll-like receptor 4 (TLR4). The binding of S100A9, S100A8/S100A9, and S100A12 to these receptors stimulates nuclear factor "kappa-light-chain-enhancer" of activated B-cells (NF-kB) signalling, which results in the upregulated expression of cytokines and pro-inflammatory factors, such as interleukin-1β (IL-1β) or tumour necrosis factor α (TNFα) [29,40,41]. Further, it was shown that S100A7, S100A8, S100A9, and S100A15 have chemotactic features, attracting neutrophils and lymphocytes [23,28,40,42,43].…”
Section: Expression and Regulationmentioning
confidence: 99%
“…The majority of extracellular S100 proteins interact with the receptor for advanced glycation end products (RAGE) and Toll-like receptor 4 (TLR4). The binding of S100A9, S100A8/S100A9, and S100A12 to these receptors stimulates nuclear factor "kappa-light-chain-enhancer" of activated B-cells (NF-kB) signalling, which results in the upregulated expression of cytokines and pro-inflammatory factors, such as interleukin-1β (IL-1β) or tumour necrosis factor α (TNFα) [29,40,41]. Further, it was shown that S100A7, S100A8, S100A9, and S100A15 have chemotactic features, attracting neutrophils and lymphocytes [23,28,40,42,43].…”
Section: Expression and Regulationmentioning
confidence: 99%
“…S100A12 gene is usually highly expressed in neutrophils at acute phase of inflammation 29 . The serum soluble form of S100A12 protein is also elevated in many inflammation-related diseases 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Since bacteria and hosts are aware of the significance of zinc, they have established a competitive relationship at the pathogen-host interface. Vertebrates employ multiple mechanisms to restrict zinc bioavailability to pathogens, which is generally termed “nutritional immunity” [ 9 , 23 , 24 ]. In particular, the host employs S100 family proteins, such as S100A7 protein psoriasis secreted by keratinocytes and S100A8/S100A9 dimer calprotectin secreted by neutrophil granulocytes to sequester zinc locally and extracellularly [ 4 , 25 ].…”
Section: Discussionmentioning
confidence: 99%